Identificação de áreas prioritárias para a conservação da biodiversidade na Microrregião Geográfica de Erechim, RS - Maia, Roberta Malinowski (2008)
The high deforestation rate of the tropical forests is considered a great challenge to the conservation programs. The reduction of the original size of the natural forest areas and the isolation caused by the fragmentation of these areas constitute great menaces to the biodiversity conservation. In doing so, the Atlantic Forest constitutes one of the more richest and threatened forests of the world with urgent need of conservation, management and recuperation. In this way, studies that they contemplate the analysis of the dynamics of landscapes constitute in fundamental activities for an integrated management of the natural resources at local and regional scale, providing subsidies for the strategic planning and for the environmental management of landscapes intensely fragmented. This work had as objective the identification and the analysis of remainders of natural and semi-natural vegetation with priority for the biodiversity conservation in Geographic Microregion of the Erechim (RS), submitted to the environmental dynamics of the loss processes, fragmentation and regeneration of habitats, as subsidy for the elaboration of conservation plans, as well as for the future amplification of the Reservation of the Biosphere of the Atlantic Forest. The methodological procedures were accomplished in SIGs IDRISI ANDES and MAPINFO PROFESSIONAL 8.0 and they involved: verification of the dynamics of the loss, fragmentation and regeneration of habitats, using images of the satellites LandSat (TM5 - 1984 and 1992) and LandSat 7 (ETM - 2002); analysis of the ecological integrity of the fragments by means of the Indicator of Ecological Integrity (IEI) with base in the referring information to the vegetation fragments, Probable Minimum Age (PMA) of the areas of the fragments and of a Edge-Core Gradient (ECG); evaluation of the susceptibility of the fragments to the environmental risks with the use of four factors (distance to the forest covering, distance to the hidrografic net, proximity to the urban centers and proximity to the roadways); culminating in the identification of areas with priority for the conservation by means of the correlation between the data of susceptibility to the environmental risks and ecological integrity of the fragments. Great losses didn't happen in the total area occupied by vegetation, which presented an amplification among the years of 1984 and 1992 (5,07%) and posterior reduction between 1992 and 2002 (5,36), staying in just 16% of the total area in 2002. More than 86% of the fragments possess inferior area to five hectares, representing 23% of the total area occupied by vegetation, and 102 fragments just possess superior area for 100 ha, corresponding 19% of the total area of vegetation. Areas that apparently didn't suffer surface alterations in the analyzed period, presenting PMA 20 years old, corresponded at 56,4% of the area of vegetation. In the analysis of ECG, it was verified that 26% of the area of the vegetation are located in the core (considered as distant area in more than 60 m starting from the edge with the not vegetated border) of the fragments, being more than 70% represented by edge area. IEI varied of zero for 95, and more than 96% of the fragments were classified between the classes of smaller integrity, representing 46% of the total area of vegetation and 1,3% of the fragments reveals areas with larger relevance for biodiversity conservation, with larger integrity of habitats. In the analysis of risks 37% of the fragments they are less subject to risks, and the areas with larger risks constitute 38% of the fragments, more than 26.000 ha of vegetation. In the analysis of areas with priority, they were identified 177 fragments with larger priority for conservation, comprehending 20.000 ha of vegetation approximately. The obtained data guide to the fragment-key identification with larger potential for the conservation of the regional biodiversity. In this context, the evaluation of the correlation between the ecological integrity and the environmental risks of the vegetation remainders, submitted to the loss processes, fragmentation and regeneration of habitats was effective in this identification, could be an alternative in short or medium period for the delimitation of areas with potential for conservation as subsidy for more specific studies, in level of populations and flora and fauna communities.